2023
DOI: 10.1002/jcla.24860
|View full text |Cite
|
Sign up to set email alerts
|

JNK/c‐Jun pathway activation is essential for HBx‐induced IL‐35 elevation to promote persistent HBV infection

Abstract: Background Immunoregulation plays pivotal roles during chronic hepatitis B virus (HBV) infection. Studies have shown that Interleukin (IL)‐35 is an important molecule associated with inadequate immune response against HBV. However, the mechanisms involved in the up‐regulation of IL‐35 expression during persistent HBV infection remain unknown. Methods In this study, we constructed a plasmid expressing the HBV X protein (pCMV‐HBx) to evaluate the relationship between HBx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…cGAMP induces IL-35 expression by B cells through an IRF3-dependent pathway that is independent of type I interferon 39 . Additionally, IL-35 expression is upregulated via JNK/c-Jun signaling mediated by HBx 40 . This pathway leads to the transactivation of the IL-35 subunits Ebi3 and p35 promoter, thereby promoting IL-35 production.…”
Section: Discussionmentioning
confidence: 99%
“…cGAMP induces IL-35 expression by B cells through an IRF3-dependent pathway that is independent of type I interferon 39 . Additionally, IL-35 expression is upregulated via JNK/c-Jun signaling mediated by HBx 40 . This pathway leads to the transactivation of the IL-35 subunits Ebi3 and p35 promoter, thereby promoting IL-35 production.…”
Section: Discussionmentioning
confidence: 99%
“…Tao et al showed, using the HepG2-NTCP HBV infection cell model, that IL-35 could promote HBV replication; IL-35 treatment led to higher levels of HBV DNA, even though no differences in serum transaminases were noted between the treated group and controls [82]. Likewise, patients with CHB seem to have higher serum levels of IL-35 when compared with controls, with IL-35 being positively correlated with HBV DNA levels [82][83][84][85][86][87][88], while it also seems to suppress the proliferation of HBV antigen-specific CTLs and interferon (IFN)-γ production both in vitro and ex vivo [89,90]. Interestingly enough, in all of these studies, liver inflammation was largely dampened, accessed either by serum transaminases or liver biopsies, highlighting the anti-inflammatory effect of IL-35.…”
Section: Interleukin 35mentioning
confidence: 99%